2021
DOI: 10.1186/s12885-021-08118-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and survival outcomes of malignant struma ovarii confined to the ovary

Abstract: Background Malignant struma ovarii (MSO) is a unique type of ovarian malignancy that data on the survival outcome is limited and management strategy remains controversial due to its extreme rarity. Methods To investigate the clinical characteristics and treatment options in patients with MSO confined to the ovary, while also evaluating the recurrent-free survival (RFS) and overall survival (OS) rate in this population, a retrospective study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 37 publications
2
65
0
Order By: Relevance
“…Papillary thyroid carcinoma is the most common type of histology in the published literature (7). Our patient also had papillary thyroid carcinoma, and a struma ovarii originating from the left ovary, which was larger than 12 cm.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Papillary thyroid carcinoma is the most common type of histology in the published literature (7). Our patient also had papillary thyroid carcinoma, and a struma ovarii originating from the left ovary, which was larger than 12 cm.…”
Section: Discussionmentioning
confidence: 63%
“…These features were all present at our patient with evidence of peritoneal metastasis on the preoperative CT record. Despite the fact that most germ cell tumors are chemosensitive, malignant struma ovarii responds poorly to chemotherapy (7); yet our patient responded well to 6 cycles of neoadjuvant chemotherapy, so that no vital extraovarian involvement was detectable on postoperative histology, only distinct fibrosis and scarring, which were originally peritoneal metastasis. As has been suggested by several authors in the literature, these implants may not be malignant peritoneal implants, but extremely well-differentiated "strumosis" corresponding to normal thyroid tissue (8,13,14).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Although their study included patients with and without metastasis, they did not evaluate risk factors for overall survival (OS). Our previous study found a similar OS rate in patients with MSO (confined to the ovary) and metastatic MSO ( 10 , 11 ). We found that age ≥55 years was a strong risk factor for OS in patients with metastatic MSO but did not find any statistically significant predictive factor for OS in patients with MSO confined to the ovary.…”
Section: Introductionmentioning
confidence: 60%